The pharmacokinetic diversity of two von Willebrand factor (VWF)/ factor VIII (FVIII) concentrates in subjects with congenital von Willebrand disease - Kessler, Craig M.; Ken, Friedman; Schwartz, Bruce A.; Gill, Joan C.; Powell, Jerry S.; for the Wilate PK Study Investigators (Thrombosis and Haemostasis, 2011)
The pharmacokinetic (PK) profiles of von Willebrand factor (VWF) /factor VIII (FVIII) concentrates are important for treatment efficacy and safety of von Willebrand disease (VWD) patients. This prospective, head-to-head, randomised crossover study compared the PK profile of a new, high purity, human plasma-derived (pd)VWF/FVIII concentrate, Wilate®, with the PK profile of an intermediate purity (pd)VWF/FVIII concentrate, Humate-P¯, in VWD patients. Subjects with inherited VWD were randomised to a single intravenous dose (40 IU/kg VWF ristocetin cofactor activity [VWF:RCo]) of Wilate® or Humate-P¯ in Period 1, and switched to the other study drug in Period 2. Each period was preceded by a washout time of ≥7 days. Coagulation factor parameters were analysed at multiple time-points. Of 22 randomised subjects, 20 had evaluable PK profiles, which indicated comparability for VWF antigen and VWF:RCo between Wilate® and Humate-P¯. The reported VWF:RCo average and terminal t1/2 of 10.4 and 15.8 hours (h), respectively, for Wilate® and 9.3 h and 12.8 h for Humate-P®, were not statistically different. Also, the mean VWF:RCo in vivo recoveries (Wilate® 1.89, Humate-P® 1.99 IU/dl per IU/kg) were similar between the two replacement therapies. Wilate® showed parallel decay curves for VWF:RCo and FVIII clotting activity (FVIII:C) over time, while FVIII:C of Humate-P® displayed a plateau between 0 and 12–24 h. This study demonstrated bioequivalent PK properties for VWF between Wilate® and Humate-P®. The PK profile of Wilate®, combined with the 1:1 VWF/FVIII ratio, theoretically should facilitate dosing and laboratory monitoring of VWF replacement to prevent bleeding in individuals with VWD.
Keywords: Factor VIII/von Willebrand factor concentrate; Humate-P®; pharmacokinetics; ristocetin co-factor; Wilate®